PENGARUH PERSONAL SELLING DAN PROMOSI PENJUALAN TERHADAP EFEKTIFITAS PENJUALAN BAN SEPEDA MOTOR PT. MEGA ANUGRAH MANDIRI - Wily Julitawaty; Frith Willy; Thomas Sumarsan Goh (JURNAL BISNIS KOLEGA, 2020)
Abstract. PT. Mega Anugrah Mandiri is a company engaged in distribution of sparepart. The decline in sales effectiveness of motorcycle tires is because the company has not yet made maximum personal selling and the company's sales promotion activities still have obstacles. In this study the population is the customers totaling 50 people. The techniques used for data collection are: interviews, documentation studies and literature studies. Data analysis techniques using Multiple Linear Regression. The results of the study indicate that personal selling and sales promotion simultaneously have a significant effect on the sales effectiveness of motorcycle tires PT. Mega Anugrah Mandiri, and partially sales promotion has a more dominant influence on the sales volume of effectiveness of motorcycle tires PT. Mega Anugrah Mandiri than personal selling. Keywords: Personal Selling, Sales Promotion, Sales Effectiveness.